The causes of the commercial cinema popularity in the context of creative industries - Staniulytė, Eivina (Creativity Studies, 2016)
This article deals with the phenomenon of the commercial cinema. The main aim is to analyze one of the creative industries’ products (films) in a perspective of different sociological and philosophical theories in order to answer the question what causes such a rapid growth and popularity of the cinema industry. In other words, the article tries to find out what relation is between the cinema industry and the culture of consumerism. It leads to assumption that the commercial cinema is capable of creating needs, desires or longings and can even enforce meanings and implications which subjects “consume”. Such thesis is analyzed through the concepts of leisure and boredom, society of makers and society of consumers, sequestration of experience and factual/contra-factual levels. First published online: 16 Dec 2015